2D Materials for All‐Solid‐State Lithium Batteries. Issue 16 (26th February 2022) - Ma, Qianyi; Zheng, Yun; Luo, Dan; Or, Tyler; Liu, Yizhou; Yang, Leixin; Dou, Haozhen; Liang, Jiequan; Nie, Yihang; Wang, Xin; Yu, Aiping; Chen, Zhongwei
Abstract: Although one of the most mature battery technologies, lithium‐ion batteries still have many aspects that have not reached the desired requirements, such as energy density, current density, safety, environmental compatibility, and price. To solve these problems, all‐solid‐state lithium batteries (ASSLB) based on lithium metal anodes with high energy density and safety have been proposed and become a research hotpot in recent years. Due to the advanced electrochemical properties of 2D materials (2DM), they have been applied to mitigate some of the current problems of ASSLBs, such as high interface impedance and low electrolyte ionic conductivity. In this work, the background and fabrication method of 2DMs are reviewed initially. The improvement strategies of 2DMs are categorized based on their application in the three main components of ASSLBs: The anode, cathode, and electrolyte. Finally, to elucidate the mechanisms of 2DMs in ASSLBs, the role of in situ characterization, synchrotron X‐ray techniques, and other advanced characterization are discussed. Abstract : This review introduces current progress of 2D materials (2DM) application in all‐solid‐state lithium batteries (ASSLB) to deal with the limitation of ASSLBs. 2DMs are applied in the different composition of the ASSLBs to enhance its performance. By summarizing the properties, synthesis, application, and characterization, this review points out the future development direction of 2DMs application in ASSLBs.